2012
DOI: 10.1021/nn302590k
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Galvanic Replacement Reaction for the Preparation of Pt/Ag Bimetallic Hollow Nanostructures with Controlled Number of Voids

Abstract: Here we report the synthesis of Pt/Ag bimetallic nanostructures with controlled number of void spaces via a tailored galvanic replacement reaction (GRR). Ag nanocubes (NCs) were employed as the template to react with Pt ions in the presence of HCl. The use of HCl in the GRR caused rapid precipitation of AgCl, which grew on the surface of Ag NCs and acted as a removable secondary template for the deposition of Pt. The number of nucleation sites for AgCl was tailored by controlling the amount of HCl added to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
205
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(211 citation statements)
references
References 46 publications
(90 reference statements)
6
205
0
Order By: Relevance
“…The GRR is one of the most efficient strategies to combine different metals in a single nanostructure. This strategy provides a remarkably simple route to produce complex metallic nanostructures with controllable hollow interiors by means of the reaction of solid metal nanostructures, used as sacrificial templates (usually Ag [19,[64][65][66][67][68], but also Cu [69][70][71], Co [70,[72][73][74][75][76][77], Pd [78,79], Mg [80] or alloys Pd-Cu [81]) and a precursor containing a relatively more noble metal ion (Au, Pd, or Pt), in a process by which the composition of the template is modified while retaining its initial morphology. Figure 2A [82].…”
Section: Synthesis Of Hollow Nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The GRR is one of the most efficient strategies to combine different metals in a single nanostructure. This strategy provides a remarkably simple route to produce complex metallic nanostructures with controllable hollow interiors by means of the reaction of solid metal nanostructures, used as sacrificial templates (usually Ag [19,[64][65][66][67][68], but also Cu [69][70][71], Co [70,[72][73][74][75][76][77], Pd [78,79], Mg [80] or alloys Pd-Cu [81]) and a precursor containing a relatively more noble metal ion (Au, Pd, or Pt), in a process by which the composition of the template is modified while retaining its initial morphology. Figure 2A [82].…”
Section: Synthesis Of Hollow Nanostructuresmentioning
confidence: 99%
“…Thus, in addition to AuAg hollow nanostructures, PtAg, PdAg [90], PdPt alloy nanocages [91,92], and trimetallic PdAuAg hollow nanostructures with control of the spatial distributions of different metals [93] can also be prepared via the GRR by simply altering the order of addition for the salt precursors, which resulted in an improved tailoring of their optical and catalytic properties. Other hollow compositions such as PtAg bimetallic nanostructures [65] and PtAg@Pt core-shell single-crystal hollow NCs [67] have also been obtained via GRR between Ag templates and a Pt salt.…”
Section: Synthesis Of Hollow Nanostructuresmentioning
confidence: 99%
“…However, because of the contribution of numerous critical factors, it is difficult to develop a precisely designed synthetic method. According to Zhang et al, the interaction between a Cu template and the replacing Pt can be confirmed by the fact that the size and number of hollow voids, which are the most important features of nanostructures formed through galvanic replacement, can be varied depending on pH and the presence of the surface-stabilizing polymer PVP [222]. These adjustments result in the formation of nanoboxes, heterodimers, multimers, and popcorn-shaped hollow voids.…”
Section: Anisotropic Nanostructuresmentioning
confidence: 99%
“…A series of electrocatalysts possessing Cu or Cu alloy cores and Pt shells have also been prepared in various experiments by using this simplified two-step seed-mediated growth method consisting of the galvanic replacement reaction [114,124,125,137]. Other core-shell-structured electrocatalysts such as Au@Pt and Ag@Pt have also been synthesized by using this principle as well [117,130]. Various examples are presented in Table 2.…”
Section: Principles and Development Of Wet Chemical Depositionmentioning
confidence: 99%